Quality of phonological representations in 54 to 77 months typically normal Persian-speaking children - Golnoosh Golmohamadi (Audiology, 2014)
Background and Aim: The ways in which words are phonologically stored and organized change with maturation. Hence, most researchers agree on the issue of phonological representations abilities evolve over time . This study aimed to determine the quality of phonological representations in normal Persian-speaking boys and girls.Methods: In this cross-sectional study , quality of phonological representations of 240 normal children at the age of 54 to 77 months was investigated using descriptive - analytical method s . The subjects were randomly selected among the children in kindergartens and preschoolers in Arak city, Iran. The study tool was a researcher-made quality of phonological representations test.Results: Significant differences were found between age groups in the scores of quality of phonological representations (p<0.01). Subjects in the first ( aged 54 to 59 months ) and fourth (aged 72 to 77 months ) age-group had the lowest and highest scores, respectively. The differences in mean scores between 54 to 59 month- and 66 to 71 month-old and between 66 to 71 month- and 72 to 77 month-old children were not significant. There were significant differences in other group mean scores (p<0.001). In all groups of syllables (i.e., words with two , three and four syllables ), o lder children have better performance. The mean scores of quality of phonological representations in the two groups of boys and girls in any of the age groups were not significantly different from each other.Conclusion: It seems that subjects' performances have improved with increase in age and gender does not affect the quality of phonological representations.